Colour and marbling of M. semimembranosus and M. longissimus thoracis et lumborum from five purebred pigs produced in Vojvodina - Jokanović Marija; Tomović Vladimir; Škaljac Snežana; Šojić Branislav; Tasić Tatjana; Ikonić Predrag; Živković Dušan; Stajić Slaviša; Pajin Biljana; Lončarević Ivana (Journal on Processing and Energy in Agriculture, 2015)
Sensory evaluation of colour and marbling of M. semimembranosus (SM) and M.   longissimus thoracis et lumborum (LTL) from five purebred pigs produced in   Vojvodina (Large White, Landrace, Duroc, Hampshire and Pietrain) was   performed. Colour was evaluated by the panellists with 6-point colour score   cards (1-pale pinkish-gray to white; 6-dark purplish-red). Marbling was   evaluated by the panellists with7-point marbling score cards (1-devoid,   6-moderate/10-abundant).The differences in the colour and in the marbling of   the SM muscles and of the LTL muscles among the five purebred pigs were not   significant (P>0.05). A darker colour was obtained for SM muscles than for   LTL muscles for all five purebred pigs, with a significant differences for   Durok (P=0.018) and Pietrain (P=0.002). The type of the muscles had no   significant effect on marbling (P>0.05). The Vojvodian pork meat showed   lighter colour than optimum for pork. According to average marbling scores   fat content in pork produced in Vojvodina was less than 2 %.